Description of a new species of Trimma (Perciformes: Gobiidae) from the Red Sea, with a discussion of the generic separation of Trimma and Priolepis, with discussion of sensory papillae terminology - Hoese, Douglass F.; Bogorodsky, Sergey V.; Mal, Ahmad O. (Zootaxa, 2015)
A new species of Pygmygoby, Trimma quadrimaculatum, n. sp., is described from the Saudi Arabian coast of the Red Sea on the basis of 16 adult specimens. It is small-sized species, with the largest examined specimen reaching only 16.8 mm SL. The new species has characteristics of both Priolepis and Trimma, and easily may be confused with Priolepis randalli and Trimma mendelssohni; it can distinguish from other species by combination of characters: dorsal-fin rays D VI + I,8; anal-fin rays I,7; longitudinal scale series 23–25; median predorsal scales 6–8 (usually 7 or 8); head naked; a pair of modified elongate papillae on nape; fifth pelvic-fin ray with 2 dichotomous branches; body with broad, irregular, brown bars, last bar posteriorly on caudal peduncle extending basally on to rays of caudal fin; head with three dark brown bars below eye; four subcutaneous dark brown spots ventrally on posterior half of body; and basal quarter of second and third membranes of first dorsal fin with diffuse dark blotch. Placement of the new species in Trimma is based on the presence of more characteristics currently associated with Trimma than with Priolepis. The generic separation of the two genera is discussed, suggesting that further work is needed to clarify the separation of these two genera.